2023
DOI: 10.1021/acsanm.3c00767
|View full text |Cite
|
Sign up to set email alerts
|

Correlating O-Vacancy and Hydrogen Spillover with Activity and Selectivity in Furfural Hydrogenation Using Nanocatalysts Comprised of Ru Nanoparticles Supported on TiO2–SiO2

Abstract: The nanoengineering of efficient and stable nanocatalysts is highly desired for sustainable biomass valorization toward the selective hydrogenation of furfural. The interaction of supports with metallic nanoparticles and oxygen vacancies has a significant role in the catalytic activity of oxide nanocatalysts. Here, by combining density functional theory (DFT) calculations and catalytic experimental data, we demonstrated that the presence of TiO 2 in Ru−SiO 2 catalysts might allow an association between oxygen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…[24][25][26] Most of the previously reported carriers are transition metal oxides, sulfides, nitrides, carbides, and hydroxides. [27][28][29][30][31][32][33] Compared with the currently used carrier, such as carbides and metal oxides, MXenes are two-dimensional acid and alkali-resistant layered transition metal carbon/nitride materials with abundant surface groups and atomic vacancy defects. 34,35 They are widely used in energy storage and conversion because of their efficient electron transfer and excellent electronic conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…[24][25][26] Most of the previously reported carriers are transition metal oxides, sulfides, nitrides, carbides, and hydroxides. [27][28][29][30][31][32][33] Compared with the currently used carrier, such as carbides and metal oxides, MXenes are two-dimensional acid and alkali-resistant layered transition metal carbon/nitride materials with abundant surface groups and atomic vacancy defects. 34,35 They are widely used in energy storage and conversion because of their efficient electron transfer and excellent electronic conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…Leandro et al have proved that the presence of TiO 2 in Ru–TiO 2 –SiO 2 created a large number of oxygen vacancies on the surface and led to the homogeneous dispersion of Ru particles. 15 Xie et al reported that the addition of SiO 2 not only increased the dispersion of Pd, but also facilitated the formation of more oxygen vacancies on the Pd–SiO 2 /TiO 2 catalyst. 16 From the above studies, it is clear that the TiO 2 coated on SiO 2 improves the dispersion of metals and the distribution of the active sites, which indicates that the TiO 2 /SiO 2 material has good modulation ability.…”
mentioning
confidence: 99%
“…The introduction of Ti(SO 4 ) 2 enriches the Ti species on the catalyst surface, and the dispersion of Ti species is highly dependent on oxygen vacancies. 15 TS-400 °C has a smaller particle size and is the most uniformly dispersed, which results in a significant reduction in the enthalpy of formation of oxygen defects and ultimately increases the number of oxygen vacancies on the surface. 26 The presence of oxygen vacancies promotes the charge transfer between TiO 2 and Ti(SO 4 ) 2 , which may increase the electron density of the bridged oxygen and the proton affinity to form more –OH groups.…”
mentioning
confidence: 99%